Prospects and Challenges of Bioeconomy Sustainability Assessment - D'Adamo, Idiano; Gastaldi, Massimo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The bioeconomy-using renewable bio-resources from the soil and sea to produce food, materials and energy-supports the achievement of sustainable development goals. Its scope is very broad as it involves primary production sectors (agriculture) and sectors that use these resources (manufacture of food, beverages and tobacco). This Special Issue, "Prospects and Challenges of Bioeconomy Sustainability Assessment", includes an Editorial, thirteen articles, ten reviews and one perspective with international authors. All papers are highly innovative and support the goals of a sustainable world.